Teachers' Value Consonance and Employee-Based Brand Equity: The Mediating Role of Belongingness and Self-Efficacy - Yang, Xianbi; Hussain Qureshi, Abrar; Kuo, Yenku; Quynh, Nguyen Ngoc; Kumar, Tribhuwan; Wisetsri, Worakamol (Frontiers in Psychology, 2022)
This study investigated the impact of value consonance on employee-based brand equity through the mediating role of teachers' self-efficacy and belongingness. For this purpose, a deductive approach was followed, and data were collected under a cross-sectional research design from academia through a questionnaire. Prior approval from the administration was sought before administrating the questionnaire on a large scale and a sample of 520 teachers was approached in the first phase. At this stage, 418 answered questionnaires were received, while in the second wave, questions related to the teacher's self-efficacy and employee-based brand equity were asked from the respondents. Out of these 418 re-distributed questionnaires, 387 were received back and after discarding the partially filled and incomplete questionnaires, the useable sample size was left as 372. Data have been analyzed by using the structural equation modeling technique, which was assessed through measurement and structural model. Results indicate that value consonance can promote positive behaviors in the workplace. Moreover, teachers with high self-efficacy can develop based on brand equity. Similarly, employees with high-value consonance develop a sense of belongingness with their academic institutes. Limitations and future directions are also discussed.